Big Data and the 21st Century Church. (March 2014) - Gutzler, Michael D.
Abstract This article observes the practices and techniques of personal data collection with analytical analysis by major retailers and social media agencies, and then offers practical ways congregations can collect data for the purposes of producing targeted messaging, evaluating the movement of individual member faith practices, and creating a model for helping members growing a deep sense of connection and commitment to congregational life.